September 11th and the Earnings of Muslims in Germany - The Moderating Role of Education and Firm Size - Thomas Cornelissen; Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2010)
While available evidence suggests that the events of September 11th negatively influenced the relative earnings of employees with Arab background in the US, it is not clear that they had similar effects in other countries. Our study for Germany provides evidence that the events also affected the relative earnings of Muslims outside the US. However, the results show that there was no uniform effect on all types of Muslims across all types of firms. Accounting for moderating factors, a significantly negative effect can only be found for low-skilled Muslims employed in small- and medium-sized firms. This conforms to theoretical expectations. Moreover, we demonstrate that defining appropriate treatment and control groups is crucial for identifying the effects.
Keywords: J71; J31; J23; 330; Muslims; September 11th; Wage Discrimination; Education; Firm Size